Experimental and Numerical Study on the Earthquake Damage of Spherical Bearings for Chinese High-Speed Railway Bridge. (10th November 2022) - Kang, Xin; Zhang, Mingliang; Qin, Hongxi; Zeng, Leqiao; Peng, Linna; Wang, Xiaoxiang; Deng, Libin; Hu, Jia; Li, Zhuo; Shao, Guangqiang; Lin, Qing
Abstract : Spherical bearings are widely applied in high-speed railway bridges (HSRBs) in China. The experimental and computational analyses were carried out to help understand the damage mechanism of these bearings under earthquake loading. A shaking table test of scaled HSRB specimen (installed with spherical bearings) was performed under the simulated earthquake action, and the intensities were, respectively, 0.15 g, 0.20 g, 0.32 g, and 0.38 g (common intensities in China) of actual earthquakes in accordance with similarity relationships. After investigating and analyzing results of the shaking table test, it is shown that no damage occurred to movable bearings in all experimental earthquake scenarios, while slight damage could be found in fixed bearings at 0.32 g earthquake. Moreover, a finite element (FE) model of the prototype HSRB was established and validated. The damage degree of spherical bearings in stronger earthquakes (i.e., 0.40 g to 1.00 g) was studied through this validated FE model. The numerical results showed that the fixed bearing was completely damaged at 0.80 g earthquake, while only moderate damage occurred to the movable bearing at that intensity.